Derivatives : the theory and practice of financial engineering - Wilmott, Paul. (Chichester : John Wiley and Sons, 1998)
This book is about: basic theory of derivatives; Path dependency; Extending black-scholes; Interest rates and products; ...
Keywords: Economics; Derivative securities -- Mathematical models; Options (Finance); Options (Finance) -- Prices -- Mathematical models